SEBUAH PEMAHAMAN DASAR HUKUM WARIS ISLAM SEBAGAI UPAYA MENGATASI PERMASALAHAN HARTA WARIS DALAM KELUARGA: A BASIC UNDERSTANDING OF ISLAMIC INHERITANCE LAW AS AN EFFORT TO OVERCOME PROBLEMS OF INHERITANCE IN THE FAMILY - Lutfi Amalia; Nurti Budiyanti; Sasqia Faradila; Yasmin Kurniawan; Baharudin Akbar (Syakhsia Jurnal Hukum Perdata Islam, 2023)
Basic understanding of Islamic inheritance law is important to overcome problems of inheritance in the family. Many families experience conflict in the distribution of inheritance due to a lack of understanding of the principles of Islamic inheritance law. This paper aims to provide a basic understanding of Islamic inheritance law and overcome problems of inheritance in the family. This writing uses a descriptive method by collecting data from literary sources related to Islamic inheritance law. Islamic inheritance law regulates the division of inheritance based on the commandments of Allah SWT in the Al-Quran. The division of inheritance in Islam refers to the principle of equality and justice between heirs. In Islam, there are two types of heirs, namely obligatory heirs and ashabul furudh heirs. Basic understanding of Islamic inheritance law can help overcome problems of inheritance in the family. With a correct understanding of the principles of Islamic inheritance law, the distribution of inheritance can be done fairly and avoid conflicts within the family.